Hydro Energy is Really a “Clean” Energy? Ecological Problems Generated by Hydropower Plants: Array - Dorobăț, Leonard Magdalin; Turtureanu, Anca; Dobrescu, Codruța Mihaela (Journal of Danubian Studies and Research, 2020)
Hydraulic energy is the ability of a physical system (running water, generally speaking river) to perform a mechanical work when flowing from a higher position to a lower position. Thanks to the water circuit in nature, maintained by the Sun's energy, hydraulic energy is a type of renewable energy. This form of energy is utilized through hydropower plants. Some of the hydroelectric plants are very large, such as the Roman-Serbian border Porţile de Fier I (Iron Gates I, in english) (the largest on the Danube) and the Portţile de Fier II (Iron Gates II). Other hydroelectric plants are medium but also very small, such as those installed on the small rivers in the Făgăraş Mountains, such as the rivers Capra, Buda, Topolog etc., some even in the Natura 2000 protected areas; more than 500 micro-hydropower plants after National Geographic. But there is a contradiction: the ecological quality of the rivers must increase, but we also need to increase the percentage of renewable energy. With their negative environmental impact, hydropower plants of any size, does not generate a so “green” energy just as it desires. Solving the discrepancy between the economically and ecologically interests, is the key to sustainable development in the Danube area.